Potential health benefits of lowering gas production and bifidogenic effect of the blends of polydextrose with inulin in a human gut model - Zhu, Liying; Guo, Fangjie; Guo, Zeyu; Chen, Xiaoqiang; Qian, Xiaoguo; Li, Xianglong; Li, Xiaoqiong; Li, Jinjun; Wang, Xin; Jia, Weiguo (Frontiers in Nutrition, 2022)
Polydextrose is a nutrient supplement and widely applied in food industry. The use of polydextrose in combination with prebiotics and probiotics has recently increased, whereas the fermentation properties of its blend have not yet been fully revealed. We evaluated the metabolic profile of polydextrose, inulin and their blends by a batch in vitro fermentation of fifteen human fecal inocula. After 24 h of fermentation, polydextrose increased the production of gas, ammonia and several short chain fatty acids including propionate and butyrate, when compared to its blends, inulin, and fructo-oligosaccharides. Furthermore, polydextrose had the slowest degradation rate of all the carbohydrates tested, consistent with its partial fermentation of in distal colon. 16S rRNA gene sequencing analysis of the gut microbiome exhibited that the significantly increased relative abundance of Clostridium_XVIII, Megamonas, Mitsuokella and Erysipelotrichaceae_incertae_sedis in polydextrose compared to other carbohydrates. On the other hand, the blends of polydextrose and inulin (1:1 or 2:1) showed reduced gas production and similar bifidogenicity to inulin alone. The blends not only had similar alpha-diversity and PCoA to inulin, but also had similar abundance of beneficial bacteria, such as Faecalibacterium and Roseburia, suggesting potential health benefits. And their low gas production was likely due to the abundance of Faecalibacterium and Anaerostipes, which were negatively correlated with the gas production. Additionally, our in vitro fermentation model shows advantages in large-scale assessment of fermentation performance.